Transforming Microteaching through Flipbook for Preparing Future Accounting Educators towards SDG 4 - Sri Widi Lestari; Khansha Sindra Irfani; Dwi Puji Astuti; Iwan Maulana (Teknodika, 2026)
his study investigates the role of digital innovation in teacher education by integrating a flipbook-based microteaching handbook into the Accounting Education program. Although printed modules remain widely used in microteaching courses, they often fail to effectively engage digital-native student teachers or support the development of essential 21st-century teaching competencies. Using a quasi-experimental pretest–posttest control group design, 60 fifth-semester students were assigned to an experimental group using the digital flipbook and a control group using printed modules. Microteaching performance was assessed through standardized rubric scores. Results showed significantly greater improvement in the experimental group, t(58)=4.37, p<0.001, with a large effect size (Cohen’s d=0.86). The experimental group achieved an 18.3% learning gain compared to 8.1% in the control group. Questionnaire data also indicated positive student perceptions regarding improved understanding (85%), confidence (92%), and motivation (88%). These findings demonstrate that flipbook-based materials not only enhance microteaching performance but also support higher engagement and digital readiness. Integrating interactive digital learning resources into teacher education can therefore contribute to achieving Sustainable Development Goal (SDG) 4, particularly Target 4.c on preparing qualified and digitally competent educators.